Comparison of revascularization and conservative treatment for hemorrhagic moyamoya disease in East Asian Countries: a single-center case series and a systematic review with meta-analysis - Zhang, Xiang-Hua; He, Jun-Hua; Zhang, Xiang-Sheng; Zhang, Jing; Wang, Cheng-jun; Dong, Yi-Peng; Tao, Wu (Frontiers in Neurology, 2023)
Objective The optimal treatment approach for hemorrhagic moyamoya disease (HMMD) remains a topic of debate, particularly regarding the comparative efficacy of revascularization versus conservative treatment. Our study, which included a single-center case series and a systematic review with meta-analysis, aimed to determine whether surgical revascularization is associated with a significant reduction in postoperative rebleeding, ischemic events, and mortality compared to conservative treatment among East Asian HMMD patients. Methods We conducted a systematic literature review by searching PubMed, Google Scholar, Wanfang Med Online (WMO), and the China National Knowledge Infrastructure (CNKI). The outcomes of surgical revascularization and conservative treatment, including rebleeding, ischemic events and mortality, were compared. The authors' institutional series of 24 patients were also included and reviewed in the analysis. Results A total of 19 East Asian studies involving 1,571 patients as well as our institution's retrospective study of 24 patients were included in the study. In the adult patients-only studies, those who underwent revascularization had significantly lower rates of rebleeding, ischemic events, and mortality compared to those who received conservative treatment (13.1% (46/352) vs. 32.4% (82/253), P < 0.00001; 4.0% (5/124) vs. 14.9% (18/121), P = 0.007; and 3.3% (5/153) vs. 12.6% (12/95), P = 0.01, respectively). In the adult/pediatric patients' studies, similar statistical results of rebleeding, ischemic events, and mortality have been obtained (70/588 (11.9%) vs. 103/402 (25.6%), P = 0.003 or <0.0001 in a random or fixed-effects model, respectively; 14/296 (4.7%) vs. 26/183 (14.2%), P = 0.001; and 4.6% (15/328) vs. 18.7% (23/123), P = 0.0001, respectively). Conclusion The current single-center case series and systematic review with meta-analysis of studies demonstrated that surgical revascularization, including direct, indirect, and a combination of both, significantly reduces rebleeding, ischemic events, and mortality in HMMD patients in the East Asia region. More well-designed studies are warranted to further confirm these findings.